Repair of a finger pulp or fingertip defect using a palmar rotatory flap pedicled with the perforating branch of the proper palmar digital artery: a retrospective study - Yongjun Du; Zhongfeng Cui; Shaoquan Pu; Zhi Peng; Sheng Lu (Journal of Orthopaedic Surgery and Research, 2023)
Abstract Background Soft tissue defects in the hand may result from trauma, oncological procedures, or severe infections. This study aimed to introduce an innovative method for repairing soft tissue defects on the palmar side of the distal segment of the affected finger or fingertip. We explored this surgical method and its curative effect on the volar rotation pedicled flap base on a perforator of the palmar digital artery (VRPF-PPDA) for repairing ventral or fingertip soft tissue defects of the distal segment of the affected finger without impairing its main blood vessels. Methods Between June 2019 and January 2021, 13 patients with finger pulp or fingertip soft tissue defects were treated with VRPF-PPDA. Flap survival rate, complication rate, two-point discrimination (2PD), and patient satisfaction were used to evaluate the efficacy of this method. The function of the affected finger was evaluated using the upper limb function evaluation method issued by the Trial Standards for Evaluation of Partial Function of the Upper Extremity of the Chinese Society for Surgery of the Hand of the Chinese Medical Association (CMA) and the Disabilities of the Arm, Shoulder, and Head (DASH) score, 6–12 months after the flap-based operation. Results Thirteen patients (18 fingers) achieved complete flap survival. The finger pulp flap was full, and no complications occurred. 2PD checks of the flaps revealed that all of them were 4–10 mm in length. According to the Trial Standards for Evaluation of Partial Function of the Upper Extremity of the Chinese Society for Surgery of the Hand of the CMA, hand function was excellent in 12 patients (17 fingers) and good in one patient, with a mean DASH score of 26.05 ± 0.45. Eleven patients selected “excellent” on the subjective satisfaction survey, while the other two selected “good.” Conclusion VRPF-PPDA surgery is a simple, effective, minimally invasive, and reliable method for repairing soft tissue defects in the distal finger pulp or fingertips. Optimal esthetic reconstruction and anatomical and functional repair can be achieved in fingers repaired using the VRPF-PPDA surgical approach.